Rancang Bangun Aplikasi Mobile Travel-Link untuk Penyedia Jasa dan Seni Pendukung Pariwisata - Yohanes, Yohanes; Linawati, Linawati; Sukadarmika, Gede (Majalah Ilmiah Teknologi Elektro; Vol 21 No 2 (2022): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2022.v21i02.P03, 2022)
This Travel-Link Mobile Application for Tourism Supporting Services and Arts is software that provides information services for tourists who are looking for service and art providers in the user's tourist destination. This application is designed as a forum for users to promote their services and arts and also users can search for service and art workers, especially in the tourism sector. To ensure that the designed application is suitable for use by end users, interface testing is carried out using the SUS (System Usability Scale) testing instrument. The results of testing the Travel-Link Mobile Application for Service Providers and Arts using the SUS test instrument showed a score of 71. With a score of 71, it can be stated that the Mobile Travel-Link application for Tourism Supporting Services and Arts is acceptable and can be a tool for people who provide services and arts in the tourism sector or are looking for service and art providers in tourist destinations. The addition of the category of service providers and tourism supporting arts can increase the value of respondents when filling out the SUS According to the questionnaire for non-tourism workers.